OPTIMIZATION OF CATAMARAN DEMIHULL FORM IN EARLY STAGES OF THE DESIGN PROCESS - Iqbal, Muhammad; Trimulyono, Andi (Department of Naval Architecture - Diponegoro University, 2014)
The amounts of research about catamaran have generated a practical formula to simplify the calculations of catamaran resistance. Ship designer will calculate the predictions of catamaran resistance rapidly. The aim of this research is focused to search the optimal demihull form where the hull form has the lowest resistance compared to other hull form models with the same displacement. To generate the different hull form, the initial hull form (parent hull) is transformed so that become some models by changing the parameter of coefficient block (Cb) in range Â±10% with Lwl, T, H, volume and displacement are constant. The transformed hull form are calculated their total resistance from Froude number (Fr) 0,2 to 0,65 with spacing hull to length ratio (S/L) 0,2 to 0,4. The results of calculation show that the optimal demihull form is Model 4 where the initial hull form Cb +5%. The model has the lowest resistance compared to other models. The comparisons of resistance Model 4 with the configurations of S/L shows that the lowest resistance is S/L 0,4, so that the optimal demihull form is Model 4 with S/L 0,4.